Understanding multiplication concept: Exploring PMRI-enhanced thematic learning using traditional games for primary teachers - Zakaria, Zakaria; Dewantara, Andi Harpeni (Jurnal Elemen, 2024)
Involving concrete situations and utilizing contexts that are closely related to students' daily lives is highly promising in creating enjoyable and meaningful mathematics learning experiences. One approach that incorporates these ideas is Pendidikan Matematika Realistik Indonesia (PMRI), which is oriented towards the mathematization of everyday experiences. This research aims to investigate how the traditional game 'maggalaceng' could support students’ understanding of multiplication in thematic learning using the PMRI approach. The method employed in this study was design research in the form of workshops involving eight teachers at a public primary school in Bone, South Sulawesi. Data were collected through classroom observations, interviews, and documentation. The results show that the teachers responded positively to integrating PMRI in thematic learning, making learning more enjoyable and meaningful. Specifically, in mathematics, the designed learning trajectory fully assists teachers in exploring alternative perspectives for teaching the concept of multiplication, progressing from the informal to the formal level as a form of repeated addition.